Optimization of Village-Owned Enterprise Management at Improving Pades in Latukan Village, Lamongan Regency - Arini Darajah; Susi Hardjati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The purpose of this study was to determine the implementation of good corporate governance in order to optimize the increase in Village Original Income of BUMDes. The population in this study was BUMDes Sumber Rejeki in Latukan Village, Karanggeneng District, Lamongan Regency. Data were obtained through observation, interviews, and documentation. The research method used was qualitative research with triangulation analysis techniques. The results of this study indicate that the implementation of good corporate governance in BUMDes in Latukan Village is good in terms of the principles of transparency, accountability, responsibility, independence and honesty. BUMDes management decisions are taken objectively without interference from parties with personal interests. BUMDes is open to community participation and does not discriminate in recruitment. BUMDes has provided adequate information as a form of transparency in BUMDes management. The implementation of accountability is still weak in human resources owned by BUMDes, especially the treasurer. The treasurer already understands the implementation of accounting according to standards. Optimization of BUMDes management can be achieved through improving the implementation of good corporate governance, which not only strengthens financial management, but also BUMDes' contribution to inclusive and sustainable village development.